Ranking and categorizing large-scale saline aquifer formations based on optimized CO2 storage potentials and economic factors. (October 2017) - Allen, Rebecca; Nilsen, Halvor M.; Andersen, Odd; Lie, Knut-Andreas
Highlights: Ranking workflow includes various criteria that reflect storage potentials and costs. Storage potentials are simulation-based, using automatic algorithms and optimization. Workflow can use different criteria and weighting, and be applied to other datasets. Abstract: The process of selecting a CO2 storage site involves evaluating many potentially suitable sites in terms of their storage potentials as well as their associated technical and economic limitations. As such, it is useful to apply a ranking scheme that makes use of several different criteria and weights each criterion based on its relative importance in the overall evaluation. In this study, we demonstrate one such possible ranking workflow using real formation datasets from CO2 Storage Atlas of the Norwegian Continental Shelf. The workflow involves computing practical storage potentials using a generic well placement scheme, mathematical optimization and vertical-equilibrium modeling, and is general in the sense that it can be applied to other formation datasets. Economic factors related to the transportation and injection of CO2 are represented by the number of injection wells required, depth of injection, and distance from a CO2 point source. The purpose of this study is not to provide formation-specific capacity estimates or efficiency factors for engineering purposes, due to the simplifying assumptions used in this work, and the fact that our specific datasets come with their own limitations (i.e., homogeneous rock properties, lack of fault data). Rather, the purpose is to demonstrate a general ranking scheme that reflects operational limitations and the economic factors likely to be involved in any commercial or demonstration CCUS project.